Heat transfer augmentation with aluminium oxide nanofluid in a plain tube and with inserts - Viswanatha Sharma, Korada; Azmi, W. H.; Bakar, R. A.; Noor, M. M.; Kadirgama, Kumaran; Reddy Prasad, D. M. (2011)
Theoretical investigation of nanofluid heat transfer under turbulent flow in a tube has been undertaken for a wide range of Reynolds number. A model is proposed for the development of eddy diffusivity equation applicable to nanofluids. The numerical result obtained from the model are compared with the experimental data different investigators. Equations are developed for the estimation of thermo-physical properties of nanofluids for input parameters viz., temperature, nano particle size and concentration. The viscosity of nanofluid is observed to increase with particle size and decrease with temperature, whereas the thermal conductivity decreases with particle size and increase with temperature. It is found that the values of heat transfer coefficients evaluated with the equations are in good agreement with the experimental results. The theoretical determination of Nusselt number for flow in a tube with twisted tape insert has been undertaken for the first time. The results obtained for flow in a tube with twisted tape are in good agreement with the experimental data. Relevant regression equations are developed for the estimation of Nusselt number. The Colburn type equation is developed for the prediction of Nusselt number where the friction factors are to be estimated with the Blasius equation;